Effects of dapagliflozin on cardiovascular and kidney events by baseline eGFR and UACR in patients with type 2 diabetes mellitus: a patient-level pooled analysis of DECLARE-TIMI 58 and DAPA-CKD trials. (3rd October 2022) - Moura, F; Wiviott, S; Chertow, G; Dwyer, J; Gause-Nilsson, I; Johansson, P; Langkilde, A; McMurray, J; Mosenzon, O; Raz, I; Rossing, P; Wheeler, D; et al.
Abstract: Background: The sodium glucose co-transporter 2 (SGLT2) inhibitor dapagliflozin reduced the risk of hospitalization for heart failure (HHF) or cardiovascular death (CVD) and the risk of kidney events in patients type 2 diabetes mellitus (T2DM) and high cardiovascular risk or chronic kidney disease in the DECLARE-TIMI 58 and DAPA-CKD trials. These events are more common at lower levels of kidney function. Combining data from the two trials creates an opportunity to examine the effect of dapagliflozin across the spectrum of baseline kidney function. Purpose: To determine the effects of dapagliflozin on HHF/CVD and kidney endpoints across a broad range of kidney function in the combined dataset. Methods: We conducted a post hoc analysis of pooled patient-level data from DECLARE and DAPA-CKD. The effects of dapagliflozin compared with placebo on HHF/CVD and kidney endpoints (defined as sustained eGFR decrease ≥40%, end-stage kidney disease, or renal death) were assessed in the combined cohorts and in subgroups of baseline eGFR (<45, 45-<60, 60-<90, ≥90 mL/min/1.73 m 2 ) and urinary albumin:creatinine ratio (UACR) (<30, 30-<300, 300-<1000, ≥1000 mg/g). Results: A total of 19, 748 patients with T2DM were included. Median (IQR) follow up time was 4.1 (3.7–4.4) years. Median eGFR was 85 (65–95) mL/min/1.73 m 2 and UACR 18.2 (7–135) mg/g. Overall, dapagliflozin reduced the risk of HHF/CVD by 18% (HR 0.82, 95% CI 0.73–0.92, p<0.001) and kidney endpoints by 40% (HR 0.60, 95% CI 0.52–0.69, p<0.001). Overall rates of HHF/CVD and kidney endpoints were higher with lower eGFR (p<0.001) and with higher UACR (p<0.001). There were consistent relative risk reductions in HHF/CVD and kidney events with dapagliflozin across eGFR (p-interaction 0.25 and 0.32, respectively, Figure 1) and UACR (p-interaction 0.29 and 0.83, respectively, Figure 2) subgroups. The absolute rate difference (ARD) with dapagliflozin for CVD/HHF ranged from 0.1 events per 1000 patient years in patients in normal categories of eGFR and UACR to 1.0–1.7 events in patients in the most abnormal categories. Likewise, the ARD for kidney events ranged from 0.2 events per 1000 patient years in the normal eGFR and UACR groups to 2.5–4.3 events in patients in the most abnormal categories. Conclusion: In this pooled analysis of pts with T2DM, there was higher risk of HHF/CVD and kidney events with lower eGFR and higher UACR. Dapagliflozin consistently reduced these events regardless of baseline eGFR and UACR, with large absolute risk reductions in patients with lower eGFR and higher UACR. Funding Acknowledgement: Type of funding sources: None.